The effect of residential environment satisfaction on depression in the elderly: Focusing on the mediating effect of stress - Park, Ji Hwan; Choi, Jeong Min (Frontiers in Public Health, 2022)
This study aimed to determine the mediating effect of stress on the relationship between residential environment satisfaction and feelings of depression in the elderly. To achieve the purpose of the study, the researcher personally conducted interviews with 250 senior citizens residing in Jeollanam-do, South Korea, from October to November 2019. SPSS version 27.0 and Hayes’ PROCESS ver. 4.0 were used for data analysis. As a result of testing the research hypothesis, a partial mediating effect of stress on the relationship between residential environment satisfaction and feelings of depression was confirmed. Based on these results, diverse practical and policy suggestions were recommended. First, a connection between barrier-free walking and public transportation linking elderly residences and major living facilities (transportation facilities, medical facilities, cultural facilities, social welfare facilities, parks, etc.) was suggested. Second, the application of a universal design was proposed when remodeling or building elderly residences. Third, policies promoting social participation of the elderly and providing assistance to increase the intimacy of their relationship with family members and neighbors are necessary to enable older adults to maintain their social relationships. Fourth, programs, such as educational schemes that provide older adults with a greater understating of stress, must be developed in parallel to facilitate stress self-management interventions. In future, it is necessary to include additional mediating or moderating variables to generalize these findings to the larger population